ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BIOLOGI BERKARAKTER KELAS XI DAN XII SMA NEGERI UNTUK STANDARISASI RPP DI KOTA SAWAHLUNTO - Nanda, Liza Ovtri; Risdawati, Renny; Nerita, Siska (STKIP PGRI Sumbar, 2013)
ABSTRACT The purpose of this research is knowing the standarisation of lesson plan that have been made by biology theachers at senior high school grades XI and XII in Sawahlunto city based on rules in IPKG-1. This research is description research that is using total sampling technique. The completing result of senior high schools lesson plan in Sawahlunto city for grades XI at present component is 48,83%, and then at grade XII at present components is 66,81%. After that the result of senior high schools lesson plan for grade XI is 66,92% with standart enough criteria, in other hand at grade XII is 71,72% with standart enough criteria. The result can be concluded if the biologys lesson plan of senior high schools at grade XI and XII in Sawahlunto city standarisation is enough.Â